Developing Strategies at the Pre-service Level to Address Critical Teacher Attraction and Retention Issues in Australian Rural, Regional and Remote Schools - Trinidad, Sue; Sharplin, E.; Lock, G.; Ledger, S.; Boyd, D.; Terry, E. (SPERA (Society for the Provision of Education in Rural Australia), 2010)
This ALTC project is a collaborative endeavour between the four public universities involved in teacher education in Western Australia (Curtin University, Edith Cowan University, Murdoch University and The University of Western Australia), focussed on improving the quality of preparation of pre-service teachers for rural, regional and remote appointments. The project will create a nexus between the theory and practice of teaching and learning by developing models of pre-service teacher rural, regional and remote practicums. The project builds on the work of other recent Australian rural education research projects (conducted through TERRAnova and the Renewing Rural and Regional Teacher Education ALTC Curriculum Project. Existing rural health collaborative models will be drawn upon to inform the developing project. The project brings together rural community and professional partnerships (including SPERA and SiMERR) that will help to sustain rural communities through the provision of quality, prepared rural, regional and remote teachers.